Light absorption enhancement in organic solar cell using non-concentric Ag:SiO2 core-shell nanoparticles - Muldarisnur, Mulda; Fahendri, F.; Perdana, Ilham; Abdullah, Zulfi; Yusfi, Meqorry (Communications in Science and Technology, 2023)
Low solar energy conversion efficiency prevents the widespread of organic solar cells; hence, metal nanoparticles have been used to overcome this problem without increasing cell thickness. We investigated light absorption enhancement in view of the embedment of Ag:SiO2 core-shell nanoparticles of different shell thicknesses, core offsets, offset orientation angles, and vertical mismatches between neighboring particles. The simulations were carried out using the finite element method. This is the first investigation in the use of asymmetric nanoparticles. At optimized conditions, absorption enhancement up to 345% compared to the one without the nanoparticles could be achieved. The enhancement was found much higher than that of the published values. The enhancement results were mainly from the increase of near-field localization and scattering in the active layer of solar cells due to the excitation of Fano resonances. The resonance occurred due to the non-symmetric nature of the core-shell nanoparticles.